Maksimalkan Efisiensi Rumah Sakit: Peran Penting Utilisasi Unit Laboratorium Kateterisasi dalam Manajemen yang Efektif - Sebuah Tinjauan Literatur - Ardyles, Ardyles (Jurnal Kesehatan Masyarakat, 2023)
This research focuses on exploring the crucial role of catheterization laboratory utilization in achieving effective hospital management, particularly in terms of operational efficiency. Through a literature review, the standards of heart catheterization service facilities and the concept of utilization in the health context are identified to outline the issues existing in the catheterization laboratory operations. This study also reviews various research that indicates factors affecting the efficiency and utilization of the catheterization laboratory, including planning and scheduling, patient readiness, and infrastructure. Initiatives to improve efficiency are also described, including a systematic approach to reduce inefficiency, the implementation of pyramid nursing schedules, and increased use of electronic scheduling systems. The conclusion of this research shows that the effective utilization and management of the catheterization laboratory can enhance hospital operational efficiency and maintain high standards of patient care.